2021
DOI: 10.3389/fnins.2021.717956
|View full text |Cite|
|
Sign up to set email alerts
|

The Mechanisms and Boundary Conditions of Drug Memory Reconsolidation

Abstract: Drug addiction can be seen as a disorder of maladaptive learning characterized by relapse. Therefore, disrupting drug-related memories could be an approach to improving therapies for addiction. Pioneering studies over the last two decades have revealed that consolidated memories are not static, but can be reconsolidated after retrieval, thereby providing candidate pathways for the treatment of addiction. The limbic–corticostriatal system is known to play a vital role in encoding the drug memory engram. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 109 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…Changes in these neurotransmitters may contribute to reinforcing addictive pathways, including nicotine. Glutamatergic ( Tzschentke and Schmidt, 2003 ; Chen et al, 2021 ), cholinergic ( Mansvelder et al, 2003 ), serotonergic ( Dhonnchadha and Cunningham, 2008 ), and GABAergic ( Xi and Stein, 2002 ) are potentially linked to drug addiction, revealing a reinforcing pathway for co-use of smoking and other addictive drugs. Harmane may inhibit addiction to these substances at high doses, as we found that harmane inhibit the expression of tyrosine hydroxylase (Th).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these neurotransmitters may contribute to reinforcing addictive pathways, including nicotine. Glutamatergic ( Tzschentke and Schmidt, 2003 ; Chen et al, 2021 ), cholinergic ( Mansvelder et al, 2003 ), serotonergic ( Dhonnchadha and Cunningham, 2008 ), and GABAergic ( Xi and Stein, 2002 ) are potentially linked to drug addiction, revealing a reinforcing pathway for co-use of smoking and other addictive drugs. Harmane may inhibit addiction to these substances at high doses, as we found that harmane inhibit the expression of tyrosine hydroxylase (Th).…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge in treating heroin addiction is relapse and is closely related to the persistence of drug reward memories ( Kalivas and Volkow, 2005 ; Robbins et al, 2008 ; Torregrossa et al, 2011 ; Wang et al, 2012 ; Preller et al, 2013 ; Chen et al, 2021a ; Ewing et al, 2021 ; Douton et al, 2022 ; Xie et al, 2022 ). Drug memories are maladaptive memories that usurp normal memory, leading to craving and relapse ( Hyman, 2005 ; Hyman et al, 2006 ; Böning, 2009 ; Alvandi et al, 2017 ; Stern et al, 2018 ; Liu et al, 2019 ; Chen et al, 2021b ). Previous studies have reported that memory traces become labile after reactivation and are re-stabilized through a process termed “reconsolidation” ( Nader, 2003 ; Nader and Einarsson, 2010 ; Alberini and Ledoux, 2013 ; Tronson and Taylor, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drug consumption in the addicted person is usually associated with an attenuated DA increase in these reward regions ( Volkow et al, 2019 ; Chen et al, 2021a ), which may be accompanied by a vicious circle of binge, sensitization, abstinence, and relapse ( Volkow and Morales, 2015 ; Mizoguchi and Yamada, 2019 ). The essence of METH dependence and relapse is pathologically based on drug-induced gene expression and synaptic plasticity changes ( Li et al, 2018 ; Chen et al, 2021b ). In recent investigations, the expression level of miRNAs was associated with molecular events at the transcriptional and post-transcriptional levels in METH addiction.…”
Section: Mirnas In Meth Addictionmentioning
confidence: 99%